Analysis of Conditional Clause Translations: Case Studies of Assassin's Creed: Revelations Novel Translation from English to Indonesian - Wahyu Budi (Journal of Research in Business, Economics, and Education, 2021)
This research is entitled Analysis of Conditional Clause Translation: Case Study of Assassin's Creed: Revelations Novel Translation from English to Indonesian which is an analysis of translation method used in translating conditional clause in Oliver Bowden’s Novel Assassin’s Creed: Revelations, translated by Melodi Violine. The purposes of this study are to find out how the translator translates the conditional clause from English to Indonesian and describes the translation techniques used by the translator. The research methodology used is descriptive qualitative. The theory used to identify the data is the translation method invented by Newmark (1988) which is depicted in a diagram called a V diagram, whereas in the translation there are two models of emphasis, namely on the source language and target language.